Peningkatan Fasilitas Air Bersih dan Sanitasi Lingkungan di Daerah Pedesaan melalui Kegiatan Kuliah Kerja Nyata - Gado, Alfridus; Tan, Valentinus (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2024)
The problems that occur at the research location are regarding clean water and sanitation such as dirty living environments, village facilities and infrastructure such as leaking clean water pipes, non-existent water storage tanks, and non-existent trash bins and RT signs in each RT, and The damaged village office monument needs attention. The location of the KKN activity is in Ngoranale Village, Bajawa District, Ngada Regency, East Nusa Tenggara Province. This KKN activity is the result of collaboration between the local village government, community, students, and Field Supervisors (DPL). The aim of this activity is for students to gain learning experience by being directly involved with the community through problems found and finding solutions to problems regarding improving clean water facilities and environmental sanitation. There are several problems encountered at the location, so there needs to be a joint effort to reduce or overcome these problems. 1) carrying out preliminary activities to build clean water storage tanks, 2) making trash cans and RT signs, 3) repairing the village office monument, and 4) community service cleaning the environment of Ngoranale Village. It is hoped that the results of this activity will provide benefits to the government and local community, and can work together for next year's KKN activities.